Development of natural cosmetics with essential oils of capim-santo and rose pepper with extraction by enzymatic process (Research, Society and Development, 2022)
Essential oils represent countless possibilities for aesthetic treatments, due to their aromatic and therapeutic characteristics. In the enzymatic extraction of oils we have the use of a complex that facilitates this process, increasing its yield. The objective of this work was to obtain lemongrass and pink pepper oils with enzymatic way, investigating their characteristics and application to develop a stable and safe dermocosmetic. During the study, the enzymatic extract was used to obtain lemongrass essential oil, with an average of 0,5g by extraction via hydrodistillation and an average of 0.6g by enzymatic treatment, which represents an increase in yield of 25% in the oil mass. Regarding the organoleptic characteristics, the lemongrass and pink pepper oil presented similarities with the plants of origin, both being considered as oils of moderate acidity, with pH between 4.0 - 5.0. The dermocosmetics from the Second Skin base (cream) and from the Carbopol Gel (serum) were analyzed in a period of 30 days, both of which presented an adequate retention factor for the incorporation of essential oils of lemongrass and pink pepper, favoring the obtaining homogeneous products, which remained unchanged in color or texture. The results found substantially evidenced the great potential of this multienzymatic extract and the proposed formulations, which represent potential products to be commercialized and used in the pharmaceutical industry.